Histological changes in the hippocampus of both cerebral hemispheres of Wistar and SHR rats under experimental chronic cerebral hypoperfusion - O. Yu. Harmatina; K. V. Rozova; А. H. Portnychenko (Zaporozhye State Medical University, 2020)
Сhronic cerebral hypoperfusion (ChCH) and arterial hypertension are the factors of risk for сerebrovascular diseases, nevertheless the underlying pathophysiological mechanisms remain unclear. Aim. To investigate histological hippocampal changes in both cerebral hemispheres of Wistar and SHR rats under the chronic cerebral hypoperfusion conditions. Маterials and methods. The experiments were carried out on male Wistar and SHR rats (6 weeks old, weight 95-100 g), which underwent occlusion of left common carotid artery to model ChCH. All manipulations were carried out in anesthetized with ketamine (60 mg/kg, i.p.) animals. In 8 weeks, the features of the hippocampal structure damage wer studied. Results. An interhemispheric difference in the level of hippocampal cells with the signs of nuclear fragmentation in the control Wistar and SHR rats with more pronounced indices in the latter on the left was shown. ChCH modeling caused hippocampal damage in both cerebral hemispheres. Under these conditions, the number of damaged hippocampal cells was higher in SHR than in Wistar rats on the left by 34.7 % (P < 0.05), and in the right hippocampus of both lines' rats the increase in such cells was almost the same. Conclusion. Taken together, these data showed that an increase in the number of neurons with the signs of nuclear fragmentation under ChCH was observed in both rat lines, and the severity of changes was greater in SHR animals, which indicates an increased risk of structural brain damage in the presence of hypertension.